The relation between central corneal thickness and axial length in a sample of Erbil population - Muhammad, Ari Hassib; Joma, Ahmed Kareem; Abdulgani, Ahmed Ismail (Zanco Journal of Medical Sciences (ZJMS), 2015)
Background and objective: A thin central corneal thickness has been reported to be a risk factor for developing primary open-angle glaucoma. This has led to a hypothesis that thinning of the cornea may be an indication of generalized weakness of the ocular integument. This study was conducted to explore the relationship between central corneal thickness and axial length in a sample of Erbil population. Methods: This is an observational cross sectional prospective study that was conducted from October 2012 to March 2013 and included 260 eyes of 130 patients. The mean age (± SD) was 37.8 ± 17.7 years for males and 35.4 ± 15.5 years for females. Axial length was measured with A-scan ultrasound biometry and central corneal thickness with ultrasonic Pachymeter. Results: The mean central corneal thickness (± SD) was 542.8 ± 36 µm in male eyes and 530.1 ± 32.5 µm in female eyes. The mean axial length (± SD) was 23.38 ± 1.1 mm in male eyes, 23.15 ± 1.2 mm in female eyes. Central corneal thickness was not correlated with axial length (Pearson correlation coefficient r = 0.037, P = 0.558). Conclusion: Central corneal thickness and axial length of the eye are two independent measurements. Thin corneas are not related to longer eye.